On the sociology of literary scandal - Abram Reitblat (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
In real literary life, a scandal is a quite familiar, if not an everyday, element, but the literary science neither analyzes it nor includes the term “scandal” in its categorical apparatus. The article attempts to demonstrate that scandal is a normal element of the literary system that plays an important stabilizing role. The norms of literary ethics are unwritten and uncodified, but, having acquired them in the course of practical activity, the vast majority of writers knows and follows them. The following basic conditions are needed for a scandal: violation of the norms accepted in literature; the publicity of this violation, i.e. presence of an observer, witness; the presence of the public, i.e. the opportunity to make the information about the misconduct public. By problematizing the norm and provoking a response, the scandal strengthens the norm.